A closer look at subnational government finances - Hans Olsson; Julia Catz (European Central Bank (ECB), 2023)
To carry out the analysis required for monetary policy, the European Central Bank (ECB) and the European System of Central Banks (ESCB) need comprehensive and reliable government finance statistics. The focus of government finance statistics has traditionally been the government as a whole (consolidated), with a particular emphasis on central government. In recent years, however, the focus on subnational government finance statistics has increased, with stories of misreporting by a number of such governments hitting the news. Moreover, subnational governments are the layer of government to which people have the closest connection through their use of services that are either subsidised or directly provided by these bodies. These two aspects prompted the authors to take a closer look at the subnational government finance statistics of all European Union (EU) countries during the period 2000-19 (before, during and after the financial crisis). Data for the year 2020 are not included in this paper to prevent the analysis being skewed by the impact of government coronavirus measures. First of all, subnational government deficit figures are scrutinised and one of the questions asked is the extent to which the financial crisis affected deficit figures. In the next section, the change in government debt is examined as a comparison with the deficit figures could provide further information on the financing of subnational government deficits. The authors assess which part of subnational government debt is held by other subsectors of government and go on to examine the financial assets held by subnational governments and their net financial worth. Has higher debt eroded subnational governments' net financial worth or has net financial worth remained relatively stable over time? The paper then delves into subnational government expenditure to establish the types of activities subnational governments spend their money on. Finally, the authors look at the sources of revenue of subnational governments to establish which part is financed by central government and which part is financed by other revenue sources.
Keywords: H11; H2; H41; H7; 330; government finance statistics; state and local government; deficit; revenue; expenditure; debt; net financial worth; financial crisis